Electroplatable polypropylene composite material as well as preparation method and application thereof
By adding small-particle talc powder and polyethylene glycol star polymer to polypropylene, the problems of poor appearance and insufficient rigidity of existing polypropylene materials are solved, and a polypropylene composite material with high rigidity and excellent electroplating appearance is achieved, meeting application needs and can replace ABS materials.
Patent Information
- Application Number
- CN202411968945.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing electroplating polypropylene materials have poor electroplating appearance and are low in rigidity, which cannot meet application needs.
By adding small-particle talc powder and polyethylene glycol star polymer to polypropylene, synergistically improves the rigidity and electroplating appearance of the material.
It significantly improves the electroplating yield of polypropylene composite materials, improves the rigidity and electroplating appearance of the material, meets application needs, and can directly replace ABS materials.
Smart Images

Figure BDA0005219056190000081 
Figure BDA0005219056190000082 
Figure BDA0005219056190000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and more specifically to an electroplatable polypropylene composite material and a preparation method and application thereof. Background Art
[0002] Metal materials have good texture and gorgeous appearance. They are generally used in high-end products such as electronic products, home appliances, office supplies, etc., with excellent touch and high-end feeling. Polymer materials have good chemical stability and are not easily corroded. In particular, they have excellent processing and molding properties, low cost, low density and other advantages. Therefore, since the birth of polymer materials, they have been rapidly applied to various industries. In order to further enhance the texture and beauty of plastic products, people have developed plastic electroplating technology to give plastic parts a metal-like appearance, which is widely used in many fields such as automobiles, electronic products, and high-end accessories.
[0003] The polymer materials used in the electroplating process are mainly polar polymers, such as ABS plastics, polycarbonate plastics, etc. Polypropylene plastics are non-polar systems, and the electroplating process is complicated. There are problems such as easy peeling of paint, surface pitting, and low yield, so they are rarely used in electroplated products. However, polypropylene materials have many advantages such as low density, low price and stability, excellent chemical resistance, and good heat resistance. Therefore, the development of polypropylene materials that can be electroplated and have good electroplating performance has great commercial application value and huge economic benefits.
[0004] Chinese patent CN1110731150A discloses a dimensionally stable, electroplatable polypropylene composite material. The invention improves the dimensional stability of the polypropylene material by adding random copolymer polypropylene, a nucleating agent, and a high-mesh modified filler mineral, while adding ethylene-octene copolymer as a toughening agent to increase the toughness of the material, and adding weakly alkaline wollastonite as an electroplating additive so that the surface of the polypropylene material can be roughened in an acidic solution, thereby realizing the feasibility of electroplating the polypropylene material. However, the invention has limited improvement on the impact resistance of the polypropylene composite material and its rigidity is relatively low. Summary of the invention
[0005] The primary purpose of the present invention is to overcome the defects and shortcomings of existing electroplatable polypropylene materials, such as poor electroplating appearance, low rigidity, and inability to meet application requirements, and to provide an electroplatable polypropylene composite material. The small-particle talc powder and the polyethylene glycol star polymer used have a synergistic effect, which can balance the rigidity and toughness of the polypropylene composite material so that the material has high rigidity and can significantly improve the electroplating appearance of the polypropylene composite material.
[0006] The second object of the present invention is to provide a method for preparing an electroplatable polypropylene composite material.
[0007] The third object of the present invention is to provide an application of an electroplatable polypropylene composite material in electronic product housings and cosmetic packaging.
[0008] The above-mentioned object of the present invention is achieved by the following technical solutions:
[0009] An electroplatable polypropylene composite material comprises the following components in parts by weight:
[0010] Polypropylene 40-60 parts, talc 30-50 parts, polyethylene glycol star polymer 3-8 parts, lubricant 1-5 parts, antioxidant 0.1-1 part;
[0011] The main chain of the polyethylene glycol star polymer is a copolymer main chain formed by anisole with a vinyl group on each of the two benzene rings, and the side chains of the polyethylene glycol star polymer are chains formed by the reaction of the aldehyde group on the benzene ring and the polyethylene glycol;
[0012] The D50 particle size of the talc is 1 to 5 μm;
[0013] The weight average molecular weight of the polyethylene glycol star polymer is 10,000 to 30,000.
[0014] The inventor unexpectedly found that adding talcum powder with small particle size and the above-mentioned polyethylene glycol star polymer containing a small amount of hydroxyl in polypropylene is conducive to the electroplating of polypropylene, further improving the electroplating yield rate of polypropylene composite materials, and also improving the rigidity of the material. Polyethylene glycol has excellent compatibility with polypropylene, can improve the toughness of the substrate, and make up for the drop in impact strength caused by the addition of talcum powder. At the same time, compared with the macromolecule of linear segment structure, the star polymer of the present invention has a smaller volume and better fluidity. The polar polyethylene glycol segment can be well compatible with polypropylene, and the polyethylene glycol segment on the surface of the composition can reduce the surface resistance of polypropylene, so that the electroplated metal layer can be better attached to the surface of the polypropylene composite. On the other hand, in the polyethylene glycol star polymer containing multiple hydroxyl groups, the polyethylene glycol segment hydroxyl group can be combined with the hydroxyl group on the surface of talcum powder by hydrogen bonding, so that talcum powder can be better dispersed in the polypropylene substrate, reducing the surface pitting and defects of the polypropylene composite material, and significantly improving the electroplating yield rate of the polypropylene composite material system.
[0015] Talc has a flake-like structure, which enables talc particles to effectively fill the gaps between polypropylene polymer chains to form a tighter network structure. The filling of talc not only reduces the free volume between polypropylene molecular chains, but also limits the movement of polypropylene molecular chains through the action of physical crosslinking points, thereby improving the rigidity of the material. Adding a small amount of talc to polypropylene can also act as a nucleating agent, promote the crystallization process of polypropylene, and refine the grains. The refinement of the grains means that the number of grain boundaries increases in the same volume, and the hindering effect of the grain boundaries on the movement of molecular chains also increases, thereby improving the rigidity of the material. The nucleating agent effect also increases the crystallinity of polypropylene, and the increase in crystallinity further enhances the rigidity of the material. By adding a certain amount of talc to the polypropylene material, the flexural modulus and flexural strength of the composite can be greatly improved, while reducing the shrinkage rate of the material to make it close to the shrinkage rate of ABS material. In some scenarios, the composite material can directly replace the ABS material without the need to re-open the mold. In addition, the addition of small-particle talcum powder can make the surface of the polypropylene material slightly and evenly roughened, which is beneficial to the subsequent electroplating process, and the metal layer is evenly attached to the surface of the part.
[0016] Preferably, the weight average molecular weight of the polyethylene glycol star polymer is 15,000-25,000.
[0017] The polyethylene glycol star polymer is prepared by the following steps:
[0018] S1. Synthesis of a divinyl monomer containing an aldehyde group: 1,2-dibromoethane is reacted with 2-hydroxy-5-vinylbenzaldehyde, and after the reaction is completed, the divinyl monomer containing an aldehyde group is purified;
[0019] S2. Polymerization of a divinyl monomer containing an aldehyde group: The divinyl monomer containing an aldehyde group obtained in step S1 is polymerized, purified after the reaction, and dried to obtain a cross-linked polymer containing an aldehyde group;
[0020] S3. Synthesis of polyethylene glycol star polymer: The cross-linked polymer containing aldehyde groups obtained in step S2 is polymerized with polyethylene glycol, and the polyethylene glycol star polymer is obtained by purification after the reaction.
[0021] Preferably, in the present invention, the weight average molecular weight of the polyethylene glycol used to prepare the branched chain is preferably 1500 to 4000. More preferably, the weight average molecular weight of the polyethylene glycol used to prepare the branched chain is more preferably 2000 to 3000. Preferably, the average molecular weight of the cross-linked polymer containing aldehyde groups in step S2 is 3000 to 5000.
[0022] The average molecular weight of the aldehyde-containing cross-linked polymer and the polyethylene glycol star polymer can be measured by a Waters-Breeze GPC instrument (Waters styragel HR1, HR3 and HR4 columns, effective measurement ranges of 100-5000, 500-30000 and 5000-600000; standard sample: polystyrene; Waters 1515 pump; Waters 2414 refractive index detector), the test temperature is 35° C., THF is the mobile phase, and the flow rate is 1 mL / min.
[0023] Preferably, the melt flow rate of the polypropylene at 230° C. and 2.16 kg is 30 to 80 g / 10 min.
[0024] In the present invention, the melt flow rate of the polypropylene can be 30g / 10min, 35g / 10min, 40g / 10min, 45g / 10min, 50g / 10min, 55g / 10min, 60g / 10min, 65g / 10min, 70g / 10min, 75g / 10min, 80g / 10min, etc., or an interval range formed by any of the above values, such as 40-50g / 10min, 45-55g / 10min, etc., but is not limited thereto.
[0025] When the melt flow rate of the polypropylene is within this range, the polypropylene composite material system has good fluidity, which is conducive to uniform mixing of the raw material components, and the preparation of polypropylene with excellent electroplating appearance and high impact resistance. The melt flow rate of the polypropylene is measured according to the standard method of "ISO 1133-1:2011".
[0026] The particle size of talcum powder affects the subsequent electroplating effect. If the particle size of talcum powder is too large, there will be more particles on the surface of the parts obtained by injection molding of the composite material, and the electroplating layer will be difficult to adhere to the surface of these small particles, resulting in the easy fall-off of the plating layer or the formation of small defects. If the particle size of talcum powder is too small, it will be difficult to disperse well and it will easily form agglomerated particles, affecting the subsequent electroplating process. In addition, talcum powder with too small a particle size is not as effective as talcum powder with coarse particle size in improving the rigidity of the polypropylene substrate.
[0027] The present invention selects talcum powder with a D50 particle size of 1 to 5 μm. Talc powder with this D50 particle size range can significantly reduce surface defects of the composite material and further improve the yield of the subsequent electroplating process.
[0028] More preferably, the D50 particle size of the talc is 1.5 to 3.5 μm.
[0029] The D50 particle size of the talcum powder can be measured with reference to GB / T 19077.1-2008 "Particle Size Analysis by Laser Diffraction Method".
[0030] Preferably, the talc is added to the composite material in the form of a masterbatch. Adding the talc in the form of a masterbatch can make the talc dispersed more evenly in the composite material. The preparation method of the masterbatch can refer to the prior art, and the talc is mixed with part of the polypropylene and the lubricant.
[0031] Preferably, the lubricant is an ester lubricant.
[0032] More preferably, the lubricant is an aliphatic stearate, for example, an oleic acid-based aliphatic polyester or an erucic acid-based aliphatic polyester.
[0033] Preferably, the antioxidant is at least one of hindered amines, hindered phenols, phosphites or thioesters.
[0034] In a specific embodiment, the hindered amine antioxidant can be UV-3808, LA-402XP, LA-402AF, etc.;
[0035] The hindered phenol antioxidant can be antioxidant 1098, antioxidant 1010, antioxidant 259, antioxidant 1076 or spiroethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate] (ADK AO-80), etc.
[0036] The phosphite antioxidant can be antioxidant 168, antioxidant PEP-36 or 627A, etc.;
[0037] The thioester antioxidant can be distearyl thiodipropionate, dilauryl thiodipropionate or pentaerythritol dodecapropylthioate.
[0038] A method for preparing a polypropylene composite material capable of being electroplated comprises the following steps:
[0039] The raw materials are mixed evenly, added into an extruder, melt-extruded, granulated, and dried to obtain the electroplatable polypropylene composite material.
[0040] More preferably, the method for preparing the electroplatable polypropylene composite material comprises the following steps: S1. preparing talcum powder, an appropriate amount of polypropylene and a lubricant into a talcum powder masterbatch;
[0041] S2. Evenly mix the talcum powder masterbatch with the remaining ingredients, melt-extrude, granulate, and dry to obtain the electroplatable polypropylene composite material.
[0042] Preferably, in step S1, the mass ratio of talc to polypropylene is 4:1.
[0043] Preferably, the temperature of the melt extrusion in step S1 is 160-210°C
[0044] Preferably, in step S1, the extruder is a twin-screw extruder, the aspect ratio of the screw is 48:1, and the screw speed is 100 r / min.
[0045] Preferably, the temperature of the melt extrusion in step S2 is 160-210°C.
[0046] Preferably, in step S2, the extruder is a twin-screw extruder, the aspect ratio of the screw is 40:1, and the screw speed is 300 r / min.
[0047] The above electroplatable polypropylene composite material is used in electronic product housings and cosmetic packaging.
[0048] More specifically, the electroplatable high-rigidity polypropylene composite material itself has a large amount of talcum powder added to it, which has good rigidity. The shrinkage rate of the composite material is close to that of ABS material. It can directly replace ABS material without updating the mold, and has broad application prospects and practical value.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] The present invention improves the surface polarity and electroplated metal adhesion of polypropylene material by adding specific polyethylene glycol star polymer, so that composite material has good electroplating characteristics. Meanwhile, because the polyethylene glycol star polymer is a flexible, three-dimensional polymer material, it has good fluidity and can improve the dispersibility of talcum powder. The compatibility of polyethylene glycol segment and polypropylene substrate is very good, the flexible segment improves the toughness of composite material system, overcomes the decline of notched impact performance of polypropylene substrate caused by the addition of talcum powder, makes the obtained polypropylene composite material have outstanding rigidity on the basis of balancing rigidity and toughness, and has excellent electroplating appearance, meets the needs of application, and its shrinkage is close to ABS material, can directly replace ABS material without updating mold, and has good production prospects. DETAILED DESCRIPTION
[0051] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.
[0052] The embodiments of the present invention adopt the following raw materials:
[0053] Polypropylene 1: PP H9018, purchased from PetroChina Lanzhou Petrochemical Company, with a melt flow rate of 54 g / 10 min at 230 °C and a load of 2.16 kg;
[0054] Polypropylene 2: PPH-MN70, purchased from Sinopec, with a melt flow rate of 78 g / 10 min at 230 °C and a load of 2.16 kg;
[0055] Polypropylene 3: PP N-Z30S was purchased from Sinopec, with a melt flow rate of 28 g / 10 min at 30 °C and a load of 2.16 kg;
[0056] Talc-1: Talc HTP Ultra5, purchased from Liaoning Aihaiyi Mining Co., Ltd., with a D50 particle size of 2.8 μm;
[0057] Talc-2: Talc TYT-777A, purchased from Haicheng Tianyuan Chemical Co., Ltd., with a D50 particle size of 14 μm;
[0058] Talc-3, talc TY90-20-A, purchased from Dongguan Sanzhi New Material Technology Co., Ltd., D50 particle size 35 μm;
[0059] Calcium carbonate, calcium carbonate MLT-2800C, purchased from Dongguan Meilitai Chemical Co., Ltd., D50 particle size of 1.4 μm;
[0060] Polyethylene glycol star copolymer-1: The weight average molecular weight of the polyethylene glycol star copolymer is 10,000, wherein the weight average molecular weight of the cross-linked polymer containing aldehyde groups in the preparation process thereof is 5,000;
[0061] The polyethylene glycol star copolymer-1 is prepared by the following preparation method:
[0062] S1. Synthesis of a divinyl monomer containing an aldehyde group: dissolving 1 mol of 2-hydroxy-5-vinylbenzaldehyde in N,N-dimethylformamide, adding potassium carbonate, stirring to obtain a mixed solution, dissolving 0.5 mol of 1,2-dibromoethane in N,N-dimethylformamide and dripping into the mixed solution, reacting under an inert atmosphere, and purifying after the reaction to obtain a divinyl monomer containing an aldehyde group;
[0063] S2. Polymerization of aldehyde-containing divinyl monomer: dissolve the aldehyde-containing divinyl monomer and azobisisobutyronitrile obtained in step S1 in tetrahydrofuran, stir and react, add tetrahydrofuran to dilute after the reaction, precipitate the polymer with methanol, and finally dry in vacuum to constant weight to obtain a cross-linked polymer containing aldehyde groups, the weight average molecular weight of which is 5000. (The cross-linked polymer containing aldehyde groups is also used to prepare polyethylene glycol star copolymer-2, polyethylene glycol star copolymer-3, polyethylene glycol star copolymer-4, polyethylene glycol star copolymer-5)
[0064] S3. Synthesis of polyethylene glycol star polymer: Mix 1 mol of the aldehyde-containing cross-linked polymer obtained in step S2 with 2.5 mol of polyethylene glycol (weight-average molecular weight is 2000) and tetrahydrofuran, and stir to react at room temperature. After the reaction is completed, pour into ice methanol to precipitate the polymer. The obtained polymer is redissolved in tetrahydrofuran and precipitated with ice methanol. This cycle is repeated 3 times to remove unreacted polyethylene glycol, thereby obtaining a polyethylene glycol star copolymer. The polyethylene glycol star copolymer has an average molecular weight of 10,000.
[0065] Polyethylene glycol star copolymer-2: The preparation steps are the same as those of polyethylene glycol star copolymer-1, except that the amount of polyethylene glycol (weight average molecular weight is 2000) added is increased to 7.5 mol, so that the weight average molecular weight of the polyethylene glycol star copolymer is 20000;
[0066] Polyethylene glycol star copolymer-3: The preparation steps are the same as those of polyethylene glycol star copolymer-1, except that the amount of polyethylene glycol (weight average molecular weight is 2000) added is increased to 12.5 mol, so that the weight average molecular weight of the polyethylene glycol star copolymer is 30000;
[0067] Polyethylene glycol star copolymer-4: its preparation steps are the same as those of polyethylene glycol star copolymer-1; the difference is that the amount of polyethylene glycol (weight average molecular weight is 2000) added is reduced to 1.5 mol, so that the weight average molecular weight of the polyethylene glycol star copolymer is 8000;
[0068] Polyethylene glycol star copolymer-5: The preparation steps are the same as those of polyethylene glycol star copolymer-1, except that the amount of polyethylene glycol (weight average molecular weight is 2000) added is increased to 47.5 mol, so that the molecular weight of the polyethylene glycol star copolymer is 100000;
[0069] Lubricant: ester lubricant, commercially available;
[0070] Antioxidant: Antioxidant 1010 and Antioxidant 168 are compounded, the mass ratio of Antioxidant 1010 to Antioxidant 168 is 1:1, commercially available;
[0071] Unless otherwise specified, the components used in the parallel embodiments and comparative examples are all the same commercially available products.
[0072] Example 1
[0073] A polypropylene composite material capable of being electroplated, wherein the weight proportions of the raw materials used are shown in Table 1.
[0074] The method for preparing the electroplatable polypropylene composite material comprises the following steps:
[0075] S1. After weighing 25% by weight of talc, polypropylene and 0.3% by weight of talc as lubricant, the mixture was uniformly mixed with talc, melt extruded, granulated and dried to obtain a talc masterbatch;
[0076] S2. The talcum powder masterbatch prepared in step S1 is uniformly mixed with the remaining polypropylene and polyethylene glycol star polymer, lubricant and antioxidant, and then added into an extruder, melt-extruded, granulated and dried to obtain the electroplatable polypropylene composite material.
[0077] Wherein, the extruders in step S1 and step S2 are both twin-screw extruders, the screw aspect ratio of the extruder in step S1 is 48:1, the screw speed is 100r / min, and the temperature of melt extrusion is 160-210°C; the screw aspect ratio of the extruder in step S2 is 40:1, the screw speed is 300r / min, and the temperature of melt extrusion is 160-210°C.
[0078] Embodiment 2 to Embodiment 9
[0079] The weight parts of the raw materials used in Examples 2 to 9 are shown in Table 1. The preparation steps of Examples 2 to 9 are the same as those of Example 1.
[0080] Table 1 Formula components of Examples 1 to 9
[0081]
[0082] Table 2 Formula components of Comparative Examples 1 to 11
[0083]
[0084]
[0085] Performance Testing
[0086] The properties of the polypropylene composite materials obtained in the above examples and comparative examples were characterized, and the specific test items, test methods and results are as follows:
[0087] (1) Izod notched impact strength test: The Izod notched impact strength test was performed using a ZBC1400-B liquid crystal plastic pendulum impact tester (MetS Industrial Systems (China) Co., Ltd.). The test standard was ISO180-2019, type A notch, the test conditions were room temperature, and the sample size was 80 mm × 10 mm × 4 mm.
[0088] (2) Flexural modulus test: The test was conducted in accordance with standard ISO178-2019. The specimen size was 80 mm × 10 mm × 4 mm. The test equipment was KRT-W20kN and the manufacturer was Kunshan KRT Testing Instrument Co., Ltd.
[0089] (3) Electroplating appearance: The material sample size is 100mm×100mm×3mm. After degreasing, roughening, neutralization, sensitization, activation, degumming and chemical nickel treatment, the appearance effect is visually inspected with a 5x magnifying glass. The definition of excellent appearance effect is: uniform coating, no pits or pits on the surface, and uniform and bright luster. The definition of good appearance effect is: uniform coating, the total number of pits and pits on the surface of the workpiece is less than 5, and the diameter of the pits and pits is less than 0.3mm. The definition of poor appearance is: uneven coating, local wrinkling, or pits and pits are always more than 5, and the diameter of pits and pits is greater than 0.3mm.
[0090] Table 3 Performance test results of Examples 1 to 9 and Comparative Examples 1 to 11
[0091]
[0092]
[0093] From the performance test results of the electroplatable polypropylene composite materials in each embodiment of Table 2, it can be seen that the polypropylene composite materials prepared in the present invention have high rigidity on the basis of achieving excellent toughness and rigidity balance, the bending modulus of the polypropylene materials can reach more than 3300 MPa, and all have excellent electroplated appearance.
[0094] From the comparison between Example 1 and Example 5, it can be seen that as the proportion of talc powder is increased, the rigidity of the system is higher, but the notched impact strength is slightly reduced.
[0095] Comparative Examples 1 and 2 add talcum powder with too large a D50 particle size. The rigidity of the composite is improved, but the notch impact is significantly reduced. In addition, because the filler particles are too large, the coating is difficult to be evenly distributed on the surface of the workpiece, and pits and wrinkles are easily formed, and the electroplating performance is reduced.
[0096] Comparative Example 3 is a star-shaped polymer of polyethylene glycol with a too small molecular weight. Its surface electroplating effect is better, but because the molecular weight of polyethylene glycol is too low, the dispersion effect on talcum powder is weak, and the toughness of the material is greatly reduced.
[0097] Comparative Example 4 is a polyethylene glycol star polymer with an excessively large molecular weight, which has a good toughening effect on the material, but the material rigidity is insufficient.
[0098] In Comparative Example 5, no talcum powder is added, and the bending modulus of the polypropylene composite material is relatively low, only 1420 MPa, and the rigidity of the system is poor.
[0099] Comparative Example 6 is a composite material without adding polypropylene glycol star polymer, and the notched impact strength of the polypropylene composite material is only 3.11 KJ / m 2 , the electroplating effect is poor.
[0100] In Comparative Example 7, the amount of talcum powder added is insufficient. The polypropylene composite material has good toughness and a good electroplated appearance, but the rigidity of the material is insufficient, and the shrinkage rate of the composite material becomes larger, which is quite different from ABS and cannot be subsequently co-molded.
[0101] In Comparative Example 8, excessive talcum powder was added, and the electroplating appearance of the polypropylene composite material was good, but the toughness of the material was insufficient and the Izod notched impact strength was low.
[0102] In comparative example 9, when too little polyethylene glycol star polymer is added, the wetting and wrapping of talc powder is insufficient, the hydroxyl groups on the surface of the composite material are also less, the appearance of the electroplating effect is reduced, and the mechanical properties are also reduced.
[0103] In Comparative Example 10, too much polyethylene glycol star polymer was added, which had a significant impact on the overall rigidity of the composite material and caused a significant decrease in the flexural modulus.
[0104] It can be seen from Comparative Example 11 that when small particles of calcium carbonate are used to replace talcum powder, although the electroplating performance is better, the bending modulus is significantly reduced.
[0105] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A polypropylene composite material capable of electroplating, characterized in that: By weight, it includes the following components: Polypropylene 40-60 parts, talc 30-50 parts, polyethylene glycol star polymer 3-8 parts, lubricant 1-5 parts, antioxidant 0.1-1 part; The main chain of the polyethylene glycol star polymer is a copolymer main chain formed by anisole with a vinyl group on each of the two benzene rings, and the side chains of the polyethylene glycol star polymer are chains formed by the reaction of the aldehyde groups on the benzene rings and polyethylene glycol; The D50 particle size of the talc is 1 to 5 μm; The weight average molecular weight of the polyethylene glycol star polymer is 10,000 to 30,000.
2. The electroplatable polypropylene composite material according to claim 1, characterized in that: The weight average molecular weight of the polyethylene glycol star polymer is 15,000 to 25,000.
3. The electroplatable polypropylene composite material according to claim 1, characterized in that: The melt flow rate of the polypropylene at 230° C. and 2.16 kg is 30 to 80 g / 10 min.
4. The electroplatable polypropylene composite material according to claim 1, characterized in that: The D50 particle size of the talc is 1.5 to 3.5 μm.
5. The electroplatable polypropylene composite material according to claim 1, characterized in that: The polyethylene glycol star polymer is prepared by the following steps: S1. Synthesis of a divinyl monomer containing an aldehyde group: 1,2-dibromoethane is reacted with 2-hydroxy-5-vinylbenzaldehyde, and after the reaction is completed, the divinyl monomer containing an aldehyde group is purified; S2. Polymerization of a divinyl monomer containing an aldehyde group: The divinyl monomer containing an aldehyde group obtained in step S1 is polymerized, purified after the reaction, and dried to obtain a cross-linked polymer containing an aldehyde group; S3. Synthesis of polyethylene glycol star polymer: The cross-linked polymer containing aldehyde groups obtained in step S2 is polymerized with polyethylene glycol, and the polyethylene glycol star polymer is obtained by purification after the reaction.
6. The electroplatable polypropylene composite material according to claim 1, characterized in that: The talc powder is added to the composite material in the form of masterbatch.
7. The electroplatable polypropylene composite material according to claim 1, characterized in that: The antioxidant is at least one of hindered amines, hindered phenols, phosphites or thioesters.
8. The method for preparing the electroplatable polypropylene composite material according to any one of claims 1 to 7, characterized in that: The steps include: The raw materials are mixed uniformly, melt-extruded, granulated and dried to obtain the electroplatable polypropylene composite material.
9. The method for preparing the electroplatable polypropylene composite material according to any one of claims 1 to 7, characterized in that: The steps include: S1. Prepare talcum powder, an appropriate amount of polypropylene and a lubricant into a talcum powder masterbatch; S2. Evenly mix the talcum powder masterbatch with the remaining ingredients, melt-extrude, granulate, and dry to obtain the electroplatable polypropylene composite material.
10. Use of the electroplatable polypropylene composite material according to any one of claims 1 to 7 in electronic product housings and cosmetic packaging.
Citation Information
Patent Citations
Polypropylene compound capable of plating and preparation method thereof
CN101418097A
Method for carrying out transparent modification on polypropylene through DBS-like transparent modified polypropylene macromolecular nucleating agent
CN117285778A
Polyamino-modified gelatin-based hydrogel and use thereof
WO2024179268A1